A hybrid logarithmic gradient algorithm for poisson noise removal in medical images - Khursheed, Shahzad; Khaliq, Amir A; Shah, Jawad Ali; Abdullah, Suheel; Khan, Sheroz (Hikari Ltd, 2014)
This paper proposes a Poisson noise removal filter consisting of a modified gradient algorithm. Square of each pixel is subtracted from the center pixel of a 3x3 window. All gradient values are log added and then square root is taken. Bias reduction is done using log value of central pixel. The method is applied on Lena image and then on some biomedical images. Recovery results show that the proposed logarithmic gradient method is computationally simple and better visually. Proposed algorithm results are also better in terms of correlation, Structural Similarity (SSIM) index and Mean Square Error (MSE). The findings have potential for applications in biomedical image diagnostics.